Untangling the Solar Wind and Magnetospheric Drivers of the Radiation Belt Electrons. Issue 4 (7th April 2022) - Wing, Simon; Johnson, Jay R.; Turner, Drew L.; Ukhorskiy, Aleksandr Y.; Boyd, Alexander J.
Abstract: Many solar wind parameters correlate with one another, which complicates the causal‐effect studies of solar wind driving of the magnetosphere. Conditional mutual information (CMI) is used to untangle and isolate the effect of individual solar wind and magnetospheric drivers of the radiation belt electrons. The solar wind density ( n sw ) negatively correlates with electron phase space density (PSD; average energy ∼1.6 MeV) with time lag ( τ ) = 15 hr. The effect of n sw has been attributed to magnetopause shadowing or other loss mechanisms, but when the effect of solar wind velocity ( V sw ) is removed, τ shifts to 7–11 hr, which is a more accurate time scale for this process. The peak correlation between V sw and PSD shifts from τ  = 30–50 to 44–56 hr, when the effect of n sw is removed. This suggests that the time scale for electron acceleration to 1–2 MeV is about 44–56 hr following V sw enhancements. The effect of n sw is significant only at L * = 4.5–6 ( L * > 6 is highly variable), whereas the effect of V sw is significant only at L * = 3.5–6.5. The peak response of PSD to V sw is the shortest and most significant at L * = 4.5–5.5. As time progresses, the peak response broadens and shifts to higher τ at higher and lower L *, consistent with local acceleration at L * = 4.5–5.5 followed by outward and inward diffusion. The outward radial diffusion time scale at L * = 5–6 is ∼40 hr per R E . Plain Language Summary: Many solar wind parameters correlate with one another, which complicates the causal‐effect studies of solar wind driving of the magnetosphere. We use conditional mutual information, which is part of information theory, to untangle and isolate the effect of individual solar wind and magnetospheric drivers of the radiation belt electrons. For example, the solar wind density negatively correlates with electron phase space density (PSD) (average energy ∼1.6 MeV) with the response time lag of 15 hr. This has been attributed to the electron loss process such as magnetopause shadowing. The time lag suggests the time scale for this process is 15 hr. However, when the effect of solar wind velocity is removed, the time lag is 7–11 hr, which is a more accurate time scale for this process. As another example, the time lag of the correlation between solar wind velocity and PSD shifts from 30 to 50 to 44–56 hr, when the effect of solar wind density is removed. This suggests that the time scale for electron acceleration to 1–2 MeV is about 44–56 hr following the solar wind velocity enhancements. We also show that the effects of solar wind velocity and density have dependence on radial distance. Key Points: The effect of n sw on radiation belt electrons is significant only at L * = 4.5–6 and not significant at L * < 4.5 The effect of V sw on radiation belt electrons is significant at L * = 3.5–6.5 and not significant at L * < 3.5 The radiation belt electron response time lag to V sw suggests local acceleration at L * = 4–5.5 followed by outward and inward diffusion